2018
DOI: 10.1186/s40842-018-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

How is neighborhood social disorganization associated with diabetes outcomes? A multilevel investigation of glycemic control and self-reported use of acute or emergency health care services

Abstract: BackgroundDiabetes management is influenced by a number of factors beyond the individual-level. This study examined how neighborhood social disorganization (i.e., neighborhoods characterized by high economic disadvantage, residential instability, and ethnic heterogeneity), is associated with diabetes-related outcomes.MethodsWe used a multilevel modeling approach to investigate the associations between census-tract neighborhood social disorganization, A1c, and self-reported use of acute or emergency health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…In addition, psychosocial factors, such as social support, health literacy, depression, and anxiety, have been associated with diabetes prevalence, adherence to selfmanagement recommendations, access to regular health care, and glycemic control (14)(15)(16)(17)(18)(19). Less evidence links the neighborhood environment to diabetes outcomes, although more recent analyses have indicated that there are possible relationships, for example through changes in access to supermarkets or improving community cohesion (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…In addition, psychosocial factors, such as social support, health literacy, depression, and anxiety, have been associated with diabetes prevalence, adherence to selfmanagement recommendations, access to regular health care, and glycemic control (14)(15)(16)(17)(18)(19). Less evidence links the neighborhood environment to diabetes outcomes, although more recent analyses have indicated that there are possible relationships, for example through changes in access to supermarkets or improving community cohesion (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…While existing evidence shows the relationship across various neighborhood factors and diabetes incidence and outcomes, 15,17,18,45 these results provide novel insights into the stress pathway through which specific neighborhood factors (specifically discrimination and crime) appear to negatively influence diabetes outcomes, namely, glycemic control. Prior work shows perceived discrimination impacts glycemic control directly through stress and indirectly through stress via self-care behaviors 29 among patients with diabetes.…”
Section: Discussionmentioning
confidence: 84%
“…Based on significant direct and indirect effects, this study suggests that neighborhood factors (particularly crime and discrimination) are indirectly associated with poorer glycemic control through higher levels of perceived stress, lower levels of self-efficacy, and completion of diabetes self-care behaviors. While existing evidence shows the relationship across various neighborhood factors and diabetes incidence and outcomes, 15,17,18,45 these results provide novel insights into the stress pathway through which specific neighborhood factors (specifically discrimination and crime) appear to negatively influence diabetes outcomes, namely, glycemic control. Prior work shows perceived discrimination impacts glycemic control directly through stress and indirectly through stress via self-care behaviors 29 among patients with diabetes.…”
Section: Discussionmentioning
confidence: 85%
“…Another possible interpretation might be that since the study populations are even more disadvantaged compared to the whole population in the study region, those disadvantaged individuals from wealthier census tracts may experience an increased level of depression and stress and in turn, had negative impacts on glycemic control. Finally, a previous study suggested people living in socioeconomically disadvantaged neighborhoods are more likely to use health care services than people from a more advantaged neighborhoods ( 35 ). Indeed, we saw that people from less advantaged communities on average participated in more classes (5.68 for first quartile of advantage index and 5.25 for fourth quartile of advantage index, Supplementary eTable 2 ) and stayed longer in the program (319 days for first quartile of advantage index and 295 days for fourth quartile of advantage index, Supplementary eTable 2 ).Therefore, a potentially higher engagement in the program among those living in more socioeconomically disadvantaged areas may have partially contributed greater HbA1C reduction in this group.…”
Section: Discussionmentioning
confidence: 98%